THE USE OF VOA SPECIAL ENGLISH AS A MEDIA TO EMPOWER STUDENTS' WRITING AND SPEAKING SKILLS IN DISTANCE LEARNING DURING COVID-19 PANDEMIC TIME - Ratih Inayah; Silpia Rahayu (PROJECT (Professional Journal of English Education), 2022)
The use of information and communication technology is very popular nowadays since face-to-face teaching and learning methods change to e-learning or distance learning as a consequence to prevent the spread of covid-19.  The purpose of this study is to investigate the use of Voice of America (VOA) Special English as a modern media in teaching and learning English. This study also explores the insight toward pros and cons of students as the main user in using VOA Special English media in learning writing and speaking. It is a qualitative descriptive research where the primary data analyzed is the development of student writing and speaking before, during, and after the implementation of VOA Special English. The participants of this research were 36 students of the first semester of English Education students in IKIP Siliwangi. The data were gained by observation, questionnaire, and interview. The result of the research showed that most of the participants (82%) agree that VOA Special English brings benefit in learning online and help them to empower their writing and speaking skill. In sum, the use of VOA Special English has a positive effect on students to empower and support their writing and speaking skill. Those skills will be very useful for developing and empowering their insight into learning English.Keywords: VOA Special English, writing, speaking, COVID-19 pandemic